Beneficial Effects of Sitostanol on the Attenuated Immune Function in Asthma Patients: Results of an In Vitro Approach - Brüll, Florence (Public Library of Science, 2012)
BACKGROUND: In vitro and animal studies have suggested that plant sterols and stanols increase cytokine production by T-helper-1 cells. This may be beneficial for patient groups characterized by a T-helper-2 dominant immune response, e.g. asthma patients. (1) to evaluate whether sitostanol induces a T-helper-1 shift in peripheral blood mononuclear cells (PBMCs) from asthma patients, and (2) to unravel the role of regulatory T-cells in this respect. METHODOLOGY/PRINCIPAL FINDINGS: PBMCs from 10 asthma patients and 10 healthy subjects were isolated and incubated with 1.2 µM sitostanol, while stimulated with 5 µg/ml PHA. Similar amounts of cholesterol were used to determine whether effects were specific for plant stanols or for sterols in general. Changes in cytokine production were measured using antibody arrays and ELISAs. Changes in regulatory T-cell population size were measured by flow cytometry, using intracellular Foxp3 staining. Sitostanol increased production of IFNγ by 6.5% and IL-2 by 6.0% compared to cholesterol (p<0.01). No changes in IL-4 and IL-13 were found. Interestingly, this effect was only present in PBMCs from asthma patients. The number of Foxp3+ cells tended to increase and their activity, measured by IL-10 production, increased after sitostanol treatment in PBMCs from asthma patients compared to controls by 32.3% (p = 0.077) and 13.3% (p<0.05), respectively. CONCLUSIONS/SIGNIFICANCE: Altogether, the sitostanol-induced Thelper-1 shift in PBMCs from asthma patients and the stimulating effects of sitostanol on Treg cell numbers and activity indicate a possible novel approach for plant stanol ester enriched functional foods in the amelioration of asthmatic symptoms. Functional effects, however, require further evaluation.